Physical rehabilitation after achilles tendon ruptures: a review of modern approaches - Мохаммад Альальван, Раад Абдул Хаді; Вітомський, Володимир; Лазарєва, Олена; Вітомська, Марина (Slobozhanskyi Herald of Science and Sport, 2017)
Ra’ad Abdul Hadi Mohammad Alalwan, Volodymyr Vitomskiy, Оlena Lazarіeva & Maryna Vitomskа Purpose: to conduct review methodological approaches to physical rehabilitation after Achilles tendon ruptures. Material & Methods: analysis and synthesis of the foreign and domestic special scientific and methodical literature on physical rehabilitation after surgical treatment of Achilles tendon rupture. Results: restore function lower limb and gait parameters is a long, complex and difficult process. Qualitative rehabilitation process should be accompanied by adequate motor mode and its extension, axial load and special exercise. The most significant differences are observed in the approach concerning types of immobilization, its term and necessity at all, timing axial load. Among the options of immobilization allocated gypsuming, a variety of cast, orthosis, splints and braces. In the later stages of rehabilitation recommendations are somewhat different of terms of basic loads such as the rise of the fingers, walking without assistive devices. Conclusion: problem of design protocol of physical rehabilitation after achilles tendon ruptures is not completely solved.